The humanity of God - Barth, Karl, 1886-1968 (John Knox Press, 1960)
In "The humanity of God", the author lays the cornerstone for his new evangelical theology by stating that the deity of God, rightly understood, includes his humanity. This is the irrefutable good news of God's acceptance of man through Christ. In "Evangelical theology in the 19th century", he examines the theology of liberalism against which he and his fellows reacted. In the last essay, "The gift of freedom", he deals with practical problems of the Christian life. The author finds the basis of evangelical ethics in the overwhelming fact that God has made made free and chosen man to be his child and a partner in his work.